Issues of Tourism Terminology in Current Modern English Languages - Ermatova Nargizaxon Qodirjon qizi, Yusupova Muxabbat Anatolevna, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
The field of tourism has evolved significantly over the past few decades, becoming one of the world’s largest industries and a vital component of many economies. As tourism expands globally, the terminology associated with it becomes increasingly complex. This paper explores the various issues surrounding tourism terminology in modern English, addressing its evolution, cultural implications, and the challenges that arise in its standardizing cultural usage.